PENGARUH MOTIVASI DAN SARANA BELAJAR TERHADAP HASIL BELAJAR GEOGRAFI SISWA KELAS XI DI SMA NEGERI 5 PADANG - Rianto, Slamet (Jurnal Spasial, 2016)
Any educational institution shall have the means, which include furniture, appliances education, media education, books and other learning resources, consumables and other equipment needed to support the learning process on a regular and ongoing. This study aims to get the data and analyze data on: 1) The effect of motivation on learning outcomes geography X1 grade students at SMAN 5 Padang. 2) The effect of a learning tool for learning outcomes geography X1 grade students at SMAN 5 Padang and 3) Effect of motivation and the means to learn together the learning outcomes geography X1 grade students at SMAN 5 Padang. This research method is descriptive correlational study because it reveals the events and relationships between variables or events are. The population in this research is class student XI.IPS SMA N 5 Padang enrolled academic year 2016/2017 with a sample of the study 84 people. The results of this study show that: 1) There is influence learning motivation towards student learning, where learning motivation variable (27.2%) of the students' learning outcomes 2) There is no effect of learning tools to the learning outcomes of students of SMAN 5 Padang with a large contribution of 10, 3%, and 3) influences of learning motivation and learning tool together significantly influence student learning outcomes, with a large contribution of 27.4%, Keywords: Motivation and Learning Means Of Learning Outcomes